The agenda of the global patient reported outcomes for multiple sclerosis (PROMS) initiative: Progresses and open questions - Zaratin, Paola; Vermersch, Patrick; Amato, Maria Pia; Brichetto, Giampaolo; Coetzee, Timothy; Cutter, Gary; Edan, Gilles; Giovannoni, Gavin; Gray, Emma; Hartung, Hans Peter; Hobart, Jeremy; Helme, Anne; et al. (Multiple sclerosis and related disorders, 2022)
On 12 September 2019, the global Patient Reported Outcome for Multiple Sclerosis (PROMS) Initiative was launched at the 35th Congress of the European Committee for Treatment and Research in Multiple Sclerosis (ECTRIMS). The multi-stakeholder PROMS Initiative is jointly led by the European Charcot Foundation (ECF) and the Multiple Sclerosis International Federation (MSIF), with the Italian Multiple Sclerosis Society (AISM) acting as the lead agency for and on behalf of the global MSIF movement. The initiative has the ambitious mission to (i) maximize the impact of science with and of patient input on the life of people affected by MS, and (ii) to represent a unified view on Patient-Reported Outcomes for MS to people affected by MS, healthcare providers, regulatory agencies and Health Technologies Assessments agencies. Equipped with an innovative participatory governance of an international and interdisciplinary network of different stakeholders, PROMS has the potential to guide future breakthroughs in MS patient-focused research and care. In this paper we present the progresses of the global PROMS Initiative and discuss the open questions that we aim to address.
Keywords: Health Personnel; Patient Reported Outcome Measures; lidé; Multiple Sclerosis; hodnocení výsledků péče pacientem; roztroušená skleróza; zdravotnický personál; Humans